Intrathecal autologous bone marrow stem cell therapy in children with autism: A randomized controlled trial. (4th November 2020) - Sharifzadeh, Narges; Ghasemi, Ali; Tavakol Afshari, Jalil; Moharari, Fatemeh; Soltanifar, Atefeh; Talaei, Ali; Pouryousof, Hamid Reza; Nahidi, Mahsa; Fayyazi Bordbar, Mohammad Reza; Ziaee, Maliheh
Abstract: Introduction: This study aimed to determine the safety and efficacy of treatment with autologous bone marrow mesenchymal stem cell (BMMSCs) compared with the routine treatment in children with autism spectrum disorder (ASD). Methods: In this ethically approved randomized controlled trial, 32 ASD children aged 5‐15 years were randomly assigned to receive either autologous BMMSC plus rehabilitation therapy and risperidone (intervention group) or rehabilitation therapy and risperidone (control group). Autologous BMMSCs were intrathecally injected in the intervention group twice in 4 weeks. Patients were assessed using childhood autism rating scale (CARS), Gilliam autism rating scale‐second edition (GARS‐II), and clinical global impression (CGI) at the baseline, as well as 6 and 12 months after intervention. Results: Overall, 32 patients in two groups of intervention (n = 14) and control (n = 18) completed the study, of which 27 (84.4%) were male. Mean age was 9.50 ± 2.14 years. The improvements in CARS total score, GARS‐II autism index, and CGI global improvement showed no significant differences between the groups over 12 months. However, the main effect for time*group interaction was significant regarding the CGI‐severity of illness, showing a significantly more pronounced improvement in the intervention group (F = 6.719; P = .002). Discussion: Intrathecal injection of autologous BMMSCs seems to be safe and feasible, but has limited clinical efficacy in treatment of children with ASD.